Implementation Of The MS-BSc Concept In Improving Teacher Competence And Quality (Descriptive Study At MTsN 4 Tabalong, South Kalimantan Province) - Afifah, Rasma; Mas'amah, Siti; Wasliman, Iim; Dianawati, Eva (International Journal of Educational Research & Social Sciences, 2022)
One of the educational problems that exist in Indonesia itself is regarding the competence of teachers who are still classified or relatively low. This is of course a big problem, because teachers in their function in the world of education need to fulfill several competencies in order to produce the expected performance and in the end be able to succeed in educational goals. in adequate conditions. A good education should not only fulfill the facilities and infrastructure, but in terms of the teachers must also be of good quality. The size of the education budget is not a determinant that can improve the quality of education. why? Because the quality or competence of teachers can still be said to be something that is a problem. In the fieldsof management of educational institutions, there are many resources needed, such as: human, facilities and infrastructure, content and knowledge, to network partnerships. In relation to the utilization of these various resources, the level of performance success can be seen from four (4) main sectors or what is often known as The Balanced Scorecard, namely: 1) Financial Aspects; 2) Stakeholder Aspect; 3) Aspects of Internal Process Implementation; 4) Overall Institutional Growth. Based on the mapping, it is known that in order to improve the competence of teachers, the education office can make various efforts including: 1) Academic and Non-Academic Achievements both institutions, teachers and students; 2) Strong managerial leadership; 3) Improving the Teacher Competency Improvement Process.